Longitudinal assessment of cardiac morphology and function following kidney transplantation. Issue 1 (24th November 2016) - Kensinger, Clark; Hernandez, Antonio; Bian, Aihua; Fairchild, Meagan; Chen, Guanhua; Lipworth, Loren; Ikizler, T. Alp; Birdwell, Kelly A.
Abstract: Background: Abnormal cardiac morphology is a risk factor for cardiovascular complications in kidney transplant patients. A supraphysiologic level of fibroblast growth factor 23 (FGF‐23) has been associated with myocardial hypertrophy in this patient population. Our aim was to evaluate the change in cardiac morphology and function following kidney transplantation and to evaluate the association between the change in FGF‐23 concentrations and cardiac morphology. Methods: We performed a longitudinal, prospective cohort study of 143 kidney transplant recipients (73% male, 75% white) measuring left ventricular (LV) mass index, left atrial (LA) volume index, and ejection fraction (EF) by echocardiography at months 1, 12, and 24 post‐transplant. FGF‐23 levels were measured at months 1 and 24 post‐transplant. Results: Unadjusted and adjusted linear mixed‐effects models were used to examine changes in outcomes over time. In the adjusted model, LV mass index ( P <.001) and LA volume index ( P <.001) decreased and EF ( P =.009) increased significantly over time. There was a significant association between decreasing FGF‐23 levels and improving LV mass index following transplant ( P =.036) in the unadjusted model; however, there was no significant relationship in the adjusted model (0.195). Conclusion: Understanding the progression of unique cardiovascular risk factors associated with kidney transplantation may provide potential opportunities to improve survival.